Gender review of climate change legislative and policy frameworks and strategies in East Africa - Aura, Ruth; Nyasimi, Mary; Cramer, Laura K.; Thornton, Philip K. (2017)
Climate change is currently acknowledged as one of the pressing global threats to the environment and humanity. This threat has moved the global community to take action on adaptation and mitigation efforts to cushion its devastating effects. Cognizance has been taken of the disproportionate impact that climate change poses to women and other vulnerable groups. The various legislative, policy and strategic frameworks on climate change available at the global and regional level is a tacit acknowledgement of the seriousness of the problem and the role of women in adaptation and mitigation strategies. For instance, through several of its decisions, the United Nations Framework Convention on Climate Change has included a focus on addressing women’s rights and gender equality with respect to climate change mitigation and adaptation strategies. In Africa, the African Union is committed to addressing climate change issues with a gender perspective. Consequently, African countries have formulated their respective climate change policies, strategies and action plans as well as green growth and low carbon strategies aimed at integrating climate change considerations into development and sectoral plans with a gendered perspective. Kenya, Uganda, Tanzania and Ethiopia are among the East African States, which have followed suit by responding to the African Union commitments to the course by developing several legislative and policy frameworks to aid the course addressing climate change.